Renal Interstitial Fluid Angiotensin I and Angiotensin II Concentrations during Local Angiotensin-Converting Enzyme Inhibition - Akira Nishiyama; Dale M. Seth; L. Gabriel Navar (2002)
ABSTRACT. It was recently demonstrated that angiotensin II (AngII) concentrations in the renal interstitial fluid (RIF) of anesthetized rats were in the nanomolar range and were not reduced by intra-arterial infusion of an angiotensin-converting enzyme (ACE) inhibitor (enalaprilat). This study was performed to determine changes in RIF AngI and AngII concentrations during interstitial administration of ACE inhibitors (enalaprilat and perindoprilat). Studies were also performed to determine the effects of enalaprilat on the de novo formation of RIF AngII elicited by interstitial infusion of AngI. Microdialysis probes (cut-off point, 30,000 D) were implanted in the renal cortex of anesthetized rats and were perfused at 2 μl/min. The effluent dialysate concentrations of AngI and AngII were measured by RIA, and reported values were corrected for the equilibrium rates at this perfusion rate. Basal RIF AngI (0.74 ± 0.05 nM) and AngII (3.30 ± 0.17 nM) concentrations were much higher than plasma AngI and AngII concentrations (0.15 ± 0.01 and 0.14 ± 0.01 nM, respectively; n = 27). Interstitial infusion of enalaprilat through the microdialysis probe (1 or 10 mM in the perfusate; n = 5 and 8, respectively) significantly increased RIF AngI concentrations but did not significantly alter AngII concentrations. However, perindoprilat (10 mM in the perfusate, n = 7) significantly decreased RIF AngII concentrations by 22 ± 4% and increased RIF AngI concentrations. Interstitial infusion of AngI (100 nM in the perfusate, n = 7) significantly increased the RIF AngII concentration to 8.26 ± 0.75 nM, whereas plasma AngI and AngII levels were not affected (0.15 ± 0.02 and 0.14 ± 0.02 nM, respectively). Addition of enalaprilat to the perfusate (10 mM) prevented the conversion of exogenously added AngI. These results indicate that addition of AngI in the interstitial compartment leads to low but significant conversion to AngII via ACE activity (blocked by enalaprilat). However, the addition of ACE inhibitors directly into the renal interstitium, via the microdialysis probe, either did not reduce RIF AngII levels or reduced levels by a small fraction of the total basal level, suggesting that much of the RIF AngII is formed at sites not readily accessible to ACE inhibition or is formed via non-ACE-dependent pathways.